مفهوم الشذوذ الجنسي وسُبل مواجهته لوقاية المجتمع الليبي من منظور الشريعة الإسلامية - Dr. Anis Saad Masoud Al-Zeer, (Sharwes Scientific Journal, 2025)
This study is considered as an attempt by the researcher to raise awareness of the issue of homosexuality in a jurisprudential form that combines the sayings of jurists in their explanation of the phenomenon of homosexuality, which has spread unnaturally throughout the Arab and Islamic world and not only in Libyan society. Rather, there have been Western calls that want to make homosexuality a legitimate matter and a human right, by explaining its concept, types, causes, and ruling in Islamic Sharia, and explaining the real work that falls on the shoulders of the elite of those working in the field of Islamic Sharia in education, teaching, preaching, guidance, and fatwas. In practice and application of the teachings of the Islamic religion, jurists, imams, preachers, and university professors specializing in Sharia science, confronting these destructive ideas that our true Islamic religion forbids, and this is what the study aimed to achieve by developing preventive and therapeutic methods to reduce this deadly disease.